Directional Whispering Gallery Mode in Microring Lasers Enabled by Tilted Azimuthal Gratings - Jinghan Chen; Adrian Abazi; Frederik van Schoonhoven; Yuji Oki; Yohei Yamamoto; Carsten Schuck; Hiroaki Yoshioka (Advanced Photonics Research)
Whispering gallery mode (WGM) microcavities, which have been extensively studied for their ultrahigh Q factors and small mode volumes, are exceptional platforms for achieving ultralow‐threshold microlasers and functional resonators. However, the rotational symmetry of these structures traps light inside, resulting in an isotropic output and limiting their use in photonics. Special structural modifications are required to achieve a unidirectional light output in WGM cavity lasers. This study introduces and experimentally validates a novel method for achieving unidirectional light propagation in lasing microrings. Spatial symmetry is broken by integrating tilted azimuthal gratings on the inner wall of the microring. Consequently, clockwise and counterclockwise propagating WGMs exhibit distinct propagation losses and backscattering coefficients depending on the tilt angle of the grating, thereby enabling a controllable direction. This advancement paves the way for enhanced applications in integrated photonics such as unidirectional light sources and orbital angular momentum emitters, thereby expanding the functional capabilities of WGM microcavities.